THE INFLUENCE OF TALENT MANAGEMENT ON EMPLOYEE PERFORMANCE - R Tatang Purnawan; Rischa Permata; Muljadi Muljadi; Siti Muthmainnah (Univesitas Muhammadiyah Tangerang, 2023)
Currently we have entered the era of society 5.0 which is accompanied by various kinds of disruptions. Disruption is an era of massive changes due to the emergence of various new innovations due to technological advances. Organizations are required to have reliable and quality human resources with high performers who are able to adapt to technological advances. Human resources are organizational assets that must be managed proactively and strategically because the biggest challenge for organizations today is excelling in talent competence. This research aims to show the factors that help increase employee performance so that organizations can achieve their goals and be able to compete with similar organizations and how to implement a talent management strategy as a strategy to develop human resources in public organizations so as to produce superior human resources in the organization. This study uses a qualitative approach with grounded theory research, namely a theoretical study that uses data from previous studies to bring out the latest research models that discuss talent management and its effect on superior HR performance. The results of this study indicate that Talent Management affects employee performance by increasing the ability to carry out roles, handle change, the ability to master knowledge and skills and improve employee personal profiles (self-confidence, communication skills or a combination of both) and the ability to concentrate. In addition, the research results also suggest that management and employees need to align management strategies and communicate the impact of talent management as an effort to develop superior human resources.Keywords : Talent Management, The Development of Superior Human Resources, employee performance.